Worker Separations in a Nonstationary Corporate Environment - Thomas J. Dohmen; Gerard A. Pfann (Institute for the Study of Labor (IZA), 2000)
This paper investigates differences in worker turnover characteristics between periods of workforce expansion and contraction in a firm. We derive a Cox proportional hazard model from a simple model of job separation based on the expected surpluses from the firm and its workers. We account for non-stationarity in the baseline hazard reversing the role of calendar time and employment duration (Imbens (1994)), and estimate the model using personnel data from a large Dutch aircraft manufacturer over a period from January 1987 until March 14th, 1996, one day before its bankruptcy. Performance evaluations, blue versus white collar employment, and career paths within the firm are found to play an important role explaining differences in turnover behavior. A generally important result is that smooth functional forms of the age effect on worker mobility can produce misleading results, blurring a better understanding of the design of early retirement schemes for corporate reorganizations.
Keywords: J63; M12; J26; 330; Turnover; personnel economics; Arbeitsmobilität; Kündigung; Zeit; Personalwirtschaft; Luftfahrtindustrie; Schätzung; Niederlande